Evaluation Analysis of the Affective Domain in the Merdeka Belajar Kurikulum Merdeka (MBKM) at State Islamic Religious Universities (PTKIN). - Andika, Arif; Yuliana, Fitri (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this article is to understand the concept of evaluating the affective domain, its challenges and implementation strategies in the independent campus learning (MBKM) curriculum at state Islamic religious universities (PTKIN). The method used is library research (Library Research) by collecting data in the form of journal articles, books, these and other sources relevant to the research theme. Data collection was carried out using documentation techniques (documentary study) and analyzed using content analysis techniques. The research results show that 1) The concept of evaluating the affective domain in Merdeka Belajar Kurikulum Merdeka (MBKM) at state Islamic religious universities (PTKIN) consists of five levels: receiving A1, responding to A2, assessing A3, organizing A4 to characterizing with an A4 value. 2) There are five challenges in evaluating the affective domain in independent learning campuses (MBKM) at state Islamic religious universities (PTKIN): Complexity of measuring affective aspects, Diversity of student backgrounds, Integration of religious and spiritual values, Limitations of evaluation instruments, Need for resources competent human resources. 3) The implementation strategy for evaluating the affective domain in Merdeka Belajar Kurikulum Merdeka (MBKM) at state Islamic religious universities (PTKIN) can be created by creating an instrument table containing the observed value aspects: aspect 1, aspect 2, aspect and so on as needed and containing percentage in each aspect. In discussion activities, for example, what is assessed are aspects of participation, contribution and class activity. The criteria are: asking questions, submitting comments on questions and Ethics.